Pengolahan Selai Buah Pala Pada Skala Industri Rumah Tangga - Sembiring, Bagem Br; Fanani, Muhammad Zainal; Haris, Helmi (Jurnal Ilmiah Pangan Halal, 2023)
Nutmeg is one of the spice commodities with the main products are seeds, mace, and essential oil. The taste of the flesh of nutmeg is sour, and the gummy is not like. The percentage of nutmeg flesh is much higher than other parts but has not utilized the optimal by people. Blanching by steaming or boiling can reduce the astringency of the nutmeg flesh, apart from soaking in a salt solution. Nutmeg pulp can processed into various products, one of them is jam. The study aims to get the jam product that the panelists like most. The activity consists of blanching (steaming and boiling) at temperatures (80 °C and 90°C) for 15 minutes. The activity stages include handling the nutmeg fruit and flesh according to the treatment, processing it into jam and organoleptic testing of jam for color, aroma, taste, texture, spreadability and pH value. The blanching process can influence the panelists’ level of preference for jam. The average score given by the panelists to the color of the jam was 5.4 (like), aroma 5.3 (like), taste 5.27 (like), and texture 5.33 (like). Blanching by boiling at 90°C for 15 minutes before processing produces the jam product most liked by the panelist